Non-commissioned Officers’ learning through Work in the Finnish Army - Pekkarinen, Otto (Proceedings of the International Conference on Networked Learning, 2016)
Lifelong learning and competence development is crucial to organizations’ success in today’s world. As part of public governance in Finland the Finnish Defence Forces view themselves as a learning organization and workplace learning is considered to be a central tool for competence development in the military. A case study about learning through work was conducted in one army unit’s three companies. The case study was a part of a larger study analysing networked learning in the conscript-training companies of the Finnish Defence Forces. The study aims to bridge the located research-gap by providing theoretical insights on the collective and individual workplace learning practices of instructors. Theoretical tools offered by knowledge-creation theory and cultural-historical activity theory were used. The knowledge-creation metaphor of learning views learning as collective artefact-mediated activity to produce something new. Cultural-historical activity theory highlights the meaning of culturally-mediated tools and artefacts in moulding the object of activity. A second important point of entry for the study was the realisation that studying individuals learning activities required to situate the learning individuals in their activity system. Drawing from these theoretical foundations workplace learning was understood as object-oriented activity in which tools and personal networks of the subjects play a major role in the individual and collective learning processes. Combining the theoretical foundations with analysing documents and norms concerning competence development in the FDF provided the starting point for an abductive process the researcher used to state the research questions. The analysis focused on the agency of the non-commissioned officers and the expansive and restrictive features of the studied companies as well as the tools, artefacts and personal networks important to learning. Empirical data was collected with semi-structured interviews and egocentric network interviews. The data was analysed with phenomenography and the visualised egocentric networks were analysed qualitatively. The preliminary results suggested that the organization viewed itself as expansive and supportive towards learning. However social affordances and active guidance towards learning were lacking. Active agency was required to succeed in the studied military organization and certain tools were well-known and commonly used in competence development, but new tools were not actively developed. It seems that there is a need to actively create and consolidate new learning practices. Personal networks play a major role in the instructors learning and they can be surprisingly broad and different, which suggests that they are carefully and personally constructed through one’s work history.